Characterization and Mapping of Groundwater Quality of Gird Region in Central India: Groundwater quality of Gird region - KS Bangar; SC Tiwari; UR Khandkar; SK Verma; N Kumawat; MJ Kaledhonkar; GS Tagore (Journal of Soil Salinity and Water Quality, 2023)
The Gird is the region of Madhya Pradesh in part of central India and is situated in the northern part of the state. It includes the districts of Bhind, Gwalior, Morena, Sheopur and Shivpuri. This region is one of the 11 agro-climatic regions of the state and is known for sorghum-wheat cropping zone. Groundwater samples were collected through survey for above mentioned districts and characterized and classified into different quality classes. The mapping of groundwater quality at 1: 50000 scale was done for the region. Out of these 302 water samples of Bhind district, 158, 20, 7 and 5 belonged to category A, B1, B2 and B3, respectively. Alkali water representation was 47, 47 and 18 in C1, C2 and C3 category in same district. Groundwater samples of Morena district (90) was categorized as good (60) and marginally saline (6), marginally alkali (20), alkali (2) and highly alkali (2). In Gwalior, 126 samples belonged to A category and 29 samples come under C2 category. Most of the groundwater samples of Sheopur district come under good category 174 (86.6%) and only 9% samples belonged to alkali water. Out of total 754 samples of Gird region, 518 (68.7%) are good water category. 51 (6.8%) samples are saline in nature of B category, whereas, 185 (24.5%) come in alkali water category. The results of the study showed that water quality of the gird region followed the trend of good> alkali water> saline water. The use of such alkali water for irrigation may create hazard of soil sodicity in long run.